2015
DOI: 10.1186/s12894-015-0023-8
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation of somatic afferent nerves in the foot increases bladder capacity in neurogenic bladder patients after sigmoid cystoplasty

Abstract: BackgroundA previous study showed that foot stimulation can delay the bladder filling sensation and increase bladder volume in healthy humans without OAB. The aim of this study was to determine whether or not electrical stimulation of somatic afferent nerves in the foot can increase bladder capacity in neurogenic bladder patients after sigmoid cystoplasty.MethodsEleven subjects underwent 30-min foot stimulation using skin surface electrodes connected to a bladder-pelvic stimulator. The electrodes were attached… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In our previous study [ 8 ], we found that foot stimulation delayed the bladder filling sensation and significantly increased BC in the patients after bladder augmentation. Comparing with baseline, the volume per CIC was significantly increased, and this long-lasting effect persisted nearly 1 day.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In our previous study [ 8 ], we found that foot stimulation delayed the bladder filling sensation and significantly increased BC in the patients after bladder augmentation. Comparing with baseline, the volume per CIC was significantly increased, and this long-lasting effect persisted nearly 1 day.…”
Section: Discussionmentioning
confidence: 89%
“…The mechanism underlying foot stimulation is unknown, but may be mediated by the nerves in the foot [ 6 8 ]. The stimulation electrodes were placed on the skin surface rather than directly on the nerves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We completed a study to determine whether or not electrical stimulation of somatic afferent nerves in the foot can increase bladder capacity in patients with NB after sigmoid cystoplasty. We showed that the bladder volume was increased from 279.4 to 361.1 mL after stimulation using the Bladder-Pelvic Stimulator [ 41 ]. A branch of the tibial nerve courses through the foot, which likely explains this effect.…”
Section: Managementmentioning
confidence: 99%
“…As a potential solution for improving the clinical efficacy, we have begun to investigate the feasibility of using TENS to electrically activate multiple nerve targets. Bladder-inhibitory responses evoked by TN stimulation is a well-documented phenomenon that has been demonstrated in anesthetized animals [ 14 16 ], and also in human participants subjected to surface stimulation of the plantar surface of the foot [ 17 , 18 ]. It has also been shown in anesthetized rats that electrical stimulation of the medial and lateral plantar nerves can evoke reflexes that (1) inhibit the bladder during electrical stimulation (i.e.…”
Section: Introductionmentioning
confidence: 99%